2017
DOI: 10.1007/s11418-017-1117-2
|View full text |Cite
|
Sign up to set email alerts
|

The anti-tumor effect of pachymic acid on osteosarcoma cells by inducing PTEN and Caspase 3/7-dependent apoptosis

Abstract: Pachymic acid (PA) is a lanostane type triterpenoid isolated from Poria cocos, which possesses an anti-tumor effect in breast cancer, prostate cancer, lung cancer, and bladder cancer cells. In this study, we investigated the effect of PA on the growth and apoptosis of human immortalized cell line (HOS) and primary osteosarcoma cells by a Cell Counting Kit-8 (CCK-8) and Annexin V and propidium iodide (PI) staining, respectively. Western blot was used to measure the expression of cleaved Caspase 3, PTEN, and AKT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…PA stimulated the production of ROS and depletion of ATP (Fig. 5b); this result was consistent with the work of Jeong et al 9) Furthermore, through the inhibition of HK2 and activation of PKM2, PA decreased the intermediate PPP level for NADPH generation and ROS scavenging, which may have contributed to the stimulation of ROS. 26) ROS can activate intrinsic and extrinsic apoptosis pathways and modulate the pro-apoptotic molecules, including MAPK, Bax, and Bcl2; moreover, it can regulate the expression levels of various transcription factors, including Sp1, AP1, and NF-κB, and other pro-oncogenic genes that are engaged in cancer cell proliferation, survival, and metastasis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PA stimulated the production of ROS and depletion of ATP (Fig. 5b); this result was consistent with the work of Jeong et al 9) Furthermore, through the inhibition of HK2 and activation of PKM2, PA decreased the intermediate PPP level for NADPH generation and ROS scavenging, which may have contributed to the stimulation of ROS. 26) ROS can activate intrinsic and extrinsic apoptosis pathways and modulate the pro-apoptotic molecules, including MAPK, Bax, and Bcl2; moreover, it can regulate the expression levels of various transcription factors, including Sp1, AP1, and NF-κB, and other pro-oncogenic genes that are engaged in cancer cell proliferation, survival, and metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…39) In the study of Jeong et al, blocking of ROS by N-acetyl-L-cysteine, which is a ROS scavenger, effectively reduced the PA-induced apoptosis. 9) Moreover, ROS-mediated ER stress is associated with apoptosis initiation, which has been observed in PAtreated lung cancer cells. 4,40) In summary, ROS generation by PA may be a fundamental mechanism for the anti-cancer activity of PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, knockdown of GSDME reduced the proapoptotic effect of Dioscin on OS 47 .In another study, Rogers et al 14 also found that the role of GSDME in targeting the mitochondria to promote caspase-3 dependent apoptosis, and the GSDME-N terminal domain can be located on cardiolipin on the mitochondrial membrane, forming a membrane pore effect, leading to the release of cytochrome-c, and then amplifying the internal signaling pathway of apoptosis. Wen et al 48 found that a lanostane type triterpenoid isolated from Poria cocos, Pachymic acid (PA),can suppress cell proliferation by the induction of caspase 3-mediated apoptosis in an immortalized cell line (HOS) and primary osteosarcoma. Li et al 49 claimed that Bcl-2 might be a direct target of miR-143.…”
Section: Assosiation Between Caspase-3 Dependent Cell Death and Cancementioning
confidence: 99%
“…The results showed that compound 1 had markedly inhibition efficiency on human primary osteosarcoma cells proliferation concentration-and time-dependently. Meanwhile, compound 1 induced cell apoptosis dose-dependently, activated caspase 3, up-regulated PTEN expression and reduced AKT phosphorylation, demonstrating that compound 1 might be effective in treating human osteosarcoma (Wen et al, 2018). The anti-tumor activity of compound 1 was observed on nasopharyngeal carcinoma (NPC) cells and it was found that compound 1 might obviously inhibit cell proliferation and dose-dependently promote the apoptosis of the human NPC cells.…”
Section: Anti-tumor Effectsmentioning
confidence: 99%